The Effect of Age at School Entry on Educational Attainment in Germany - Michael Fertig; Jochen Kluve (Institute for the Study of Labor (IZA), 2005)
Determining the optimal age at which a child should enter school is a controversial topic in education policy. In particular, German policy makers, pedagogues, parents, and teachers have since long discussed whether the traditional, established age of school entry at 6 years remains appropriate. Policies of encouraging early school entry or increased consideration of a particular child's competency for school ("Schulfähigkeit") have been suggested. Using a dataset capturing children who entered school in the late 1960s through the late 1970s, a time when delaying enrolment was common, we investigate the effect of age at school entry on educational attainment for West and East Germany. Empirical results from linear probability models and matching suggest a qualitatively negative relation between the age at school entry and educational outcomes both in terms of schooling degree and probability of having to repeat a grade. These findings are likely driven by unobserved ability differences between early and late entrants. We therefore use a cut-off date rule and the corresponding age at school entry according to the regulation to instrument the actual age at school entry. The IV estimates suggest there is no effect of age at school entry on educational performance.
Keywords: J13; I21; 330; schooling; matching; instrumental variables; Schulrecht; Schüler; Kinder; Bildungsniveau; Schätzung; Deutschland; Alte Bundesländer; Neue Bundesländer